2018
DOI: 10.1021/acsnano.8b02152
|View full text |Cite
|
Sign up to set email alerts
|

Multidirection Piezoelectricity in Mono- and Multilayered Hexagonal α-In2Se3

Abstract: Piezoelectric materials have been widely used for sensors, actuators, electronics, and energy conversion. Two-dimensional (2D) ultrathin semiconductors, such as monolayer h-BN and MoS with their atom-level geometry, are currently emerging as new and attractive members of the piezoelectric family. However, their piezoelectric polarization is commonly limited to the in-plane direction of odd-number ultrathin layers, largely restricting their application in integrated nanoelectromechanical systems. Recently, theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
229
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 257 publications
(253 citation statements)
references
References 37 publications
18
229
5
1
Order By: Relevance
“…[ 26 ] Xue et al obtained an out‐of‐plane piezoelectric coefficient of 0.34 pm V −1 for monolayer α‐In 2 Se 3 , which itself contains odd (five) number of atomic layers. [ 27 ] Another interesting category of 2D materials are Janus monolayers, which can show stronger piezoelectricity than their standard TMDC counterparts. [ 28 ] These developments bring to fore artificial approaches to create piezoelectricity in materials that are not intrinsically so.…”
Section: Figurementioning
confidence: 99%
“…[ 26 ] Xue et al obtained an out‐of‐plane piezoelectric coefficient of 0.34 pm V −1 for monolayer α‐In 2 Se 3 , which itself contains odd (five) number of atomic layers. [ 27 ] Another interesting category of 2D materials are Janus monolayers, which can show stronger piezoelectricity than their standard TMDC counterparts. [ 28 ] These developments bring to fore artificial approaches to create piezoelectricity in materials that are not intrinsically so.…”
Section: Figurementioning
confidence: 99%
“…However, monolayer BP devices are almost impossible to fabricate because of their rapid oxidation in air. Xue et al reported the existence of piezoelectricity in multilayered α‐In 2 Se 3 and were the first to explain the piezoelectric mechanism in multilayer 2D materials . Similarly, the structure of multilayer BP can be analyzed in terms of non‐neutralized polarity of bilayers and the piezoelectricity of multilayer BP devices can then be elaborated on detail.…”
mentioning
confidence: 99%
“…Third, unlike black phosphorus which is also a direct bandgap 2D material, thin In 2 Se 3 flakes are very stable in air, which is very important for practical applications. Recently, there has been pioneering work on the use of 2D In 2 Se 3 in piezoelectronics [24,25], optoelectronics [26], and photovoltaics [27]. We note that these reported 2D In 2 Se 3 materials have small domain sizes (from a few to tens of micrometers, Figure 1(a) and Table S1) [28][29][30].…”
Section: Introductionmentioning
confidence: 92%